PRESERVATION AND CONSERVATION OF AL-QUR'AN COLLECTION IN NORTH SUMATERA AL-QUR™AN HISTORY MUSEUM AS HISTORICAL STUDY - Santri, Nur; Ritonga, Sakti (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2023)
This research study examines the results of the preservation and conservation of the Koran collection at the Al-Quran History Museum in North Sumatra as a study of historical studies. The North Sumatra Al-Qur'an History Museum is a museum founded by Dr. Phil Ichwan Azhari, M.S which was inaugurated by Governor Edy Rahmayadi in 2019. The Al-Qur'an Museum was established with the aim of increasing public knowledge that North Sumatra had Islamic history and civilization in the past. This study used a descriptive qualitative research method with the researcher then functioning as a key tool. Data collection uses literature studies, observations, document analysis and interviews. The results of the study show that the collection of Al-Qur'an in the Museum of Al-Qur'an History of North Sumatra which has been preserved and conserved can be used as material for studying historical studies that can be utilized by historians, history teachers, or history enthusiasts and others, especially through historical methods namely heuristics, external criticism and internal criticism, interpretation, and historiography. The hope is that by utilizing the Al-Qur'an collection at the Museum of Al-Qur'an History in North Sumatra, it will further enrich the treasures of works of Islamic history.